2005
DOI: 10.1017/s0031182005007614
|View full text |Cite
|
Sign up to set email alerts
|

Significant familial differences in the frequency of abortion and Toxoplasma gondii infection within a flock of Charollais sheep

Abstract: A study was carried out to investigate the frequencies of abortion and congenital Toxoplasma gondii infection within 27 families (765 individuals) of a pedigree Charollais sheep flock maintained on a working farm in Worcestershire, UK, since 1992. Pedigree lambing records were analysed to establish the frequency of abortion for each family. The frequency of congenital infection was determined for each family by PCR analysis of tissue samples taken from newborn lambs. A total of 155 lambs were tested for congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 18 publications
1
49
1
1
Order By: Relevance
“…There are a lot of unclear aspects of its congenital importance. According to the results of the recent researches in the UK, Toxoplasma vertical transmission can occur more frequently than what was previously thought (Duncanson et al 2001;Morely et al 2005Morely et al , 2007Hide et al 2009;Innes et al 2009;Dubey 2009), but Edwards and Dubey (2013) reported that this problem is resolved in the involved flock after one year or two years. If this kind of abortion takes place, it needs to be dealt with either by taking prophylactic measures or culling infected sheep from the flock which is more economical.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are a lot of unclear aspects of its congenital importance. According to the results of the recent researches in the UK, Toxoplasma vertical transmission can occur more frequently than what was previously thought (Duncanson et al 2001;Morely et al 2005Morely et al , 2007Hide et al 2009;Innes et al 2009;Dubey 2009), but Edwards and Dubey (2013) reported that this problem is resolved in the involved flock after one year or two years. If this kind of abortion takes place, it needs to be dealt with either by taking prophylactic measures or culling infected sheep from the flock which is more economical.…”
Section: Discussionmentioning
confidence: 96%
“…It was first described by Hartley et al (1954) which even today is known as one of the major causes of sheep abortion world wide (Buxton 1991). Another characteristic of vertical transmission of T. gondii is that this kind of transmission can occur more frequently than what was previously thought (Duncanson et al 2001;Morely et al 2005Morely et al , 2007Hide et al 2009;Innes et al 2009;Dubey 2009). …”
Section: Introductionmentioning
confidence: 94%
“…Further recent studies on sheep have revealed that congenital transmission may be sufficient to explain the maintenance of T. gondii in natural populations of sheep without requiring new infections by oocysts secreted by cats. [22][23][24][25] In the case of these sheep studies, it was demonstrated that PCR detection of T. gondii DNA in the umbilical cord was a good indicator of infection when aborted lamb brain tissue was compared in the same animal. Nevertheless, a challenge to be encountered in humans (as may be the case in sheep and other animals) is to understand whether these individuals are truly asymptomatic carriers of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…22 Appropriate protocols were used at each stage of the DNA purification and any subsequent PCR amplifications to prevent cross-contamination as described previously. 21,23,25,35 PCR detection of T. gondii Detection of T. gondii was carried out using a nested PCR amplification of both surface antigen gene 1 (sag 1) as described previously 24,36 and surface antigen gene 3 (sag 3) 37 with subsequent modifications. 38 Pure T. gondii DNA from RH, Martin, 17695 and COR strains were used as positive controls in all PCR experiments.…”
Section: Sample Collection and Ethical Approvalmentioning
confidence: 99%
See 1 more Smart Citation